To fill in the blanks following the steps to solve the equation \( 5x - 12 - 6x = -10x + 7 - 1 \), let's proceed step by step.
Step One: Combine Like Terms
On the left side:
- \( 5x - 6x = -x \)
- Thus, the left side simplifies to \(-x - 12\).
On the right side:
- Combine \( 7 - 1 \) which equals \( 6 \).
- Thus, the right side simplifies to \(-10x + 6\).
So, after combining like terms, we get: \[ -x - 12 = -10x + 6 \]
Step Two: Isolate the variable
Next, we will add \( 10x \) to both sides to get all terms involving \( x \) on one side: \[ -x + 10x - 12 = 6 \] This simplifies to: \[ 9x - 12 = 6 \]
Step Three: Solve for \( x \)
Now add \( 12 \) to both sides: \[ 9x - 12 + 12 = 6 + 12 \] This simplifies to: \[ 9x = 18 \]
Step Four: Divide to find \( x \)
Finally, divide both sides by \( 9 \): \[ x = \frac{18}{9} \] Which simplifies to: \[ x = 2 \]
Summary of Steps:
- Combine like terms:
- From \( 5x - 12 - 6x = -10x + 7 - 1 \) to \( -x - 12 = -10x + 6 \)
- Isolate the variable:
- From \( -x - 12 = -10x + 6 \) to \( 9x - 12 = 6 \)
- Solve for \( x \):
- From \( 9x - 12 = 6 \) to \( 9x = 18 \)
- Divide to find \( x \):
- From \( 9x = 18 \) to \( x = 2 \)
The value of \( x \) is \( 2 \).